The Impact of the Arab Spring on the Tunisian Economy - Matta, Samer (World Bank, Washington, DC, 2016)
This paper uses Synthetic Control Methodology to estimate the output loss in Tunisia as a result of the "Arab Spring." The results suggest that the loss was 5.5 percent, 5.1 percent, and 6.4 percent of GDP in 2011, 2012, and 2013 respectively. These findings are robust to a series of tests, including placebo tests, and are consistent with those from an Autoregressive Distributed Lag Model of Tunisia's economic growth. Moreover, this paper finds that investment was the main channel through which the economy was adversely impacted by the Arab Spring.